Peningkatan Produksi dan Pendapatan Petani Jagung Pulut melalui Aplikasi Pupuk Organik Abu Sabut Kelapa - Mamondol, Marianne Reynelda; Taariwuan, Silvany Annatje (University of Merdeka Malang, 2021)
This community service was carried out at Poso Regency in June to November 2019. Its purpose was to provide training and assistance to partner in utilizing and processing coconut fiber as agricultural waste into organic fertilizer of ash to be applied to waxy corn crop. The method of activity includes: (1) Explanation regarding the process of making organic fertilizer with raw materials of coconut fiber wastes, and economic aspect of utilizing coconut ash organic fertilizer; (2) Production activity in the form of the coconut ash organic fertilizer processing training, the fertilizer application to crop, and profit farming analysis to measure turnover increasing; (3) Partner assistance during the training and productions processes. Partner consists of farmer who belongs to the category of economically productive. Results demonstrate that the program implementation has given improvement to technical and economic achievements of partner’s farming. The improvement of waxy corn production was from 0.90 tonnes/hectare to 3.912 tonnes/hectare, whereas the increased farm profits was from IDR 2,600,000/ha/planting season to IDR 16,066,000/ha/planting season. A high level of partner’s satisfaction to cooperation and activity outcome on partner’s productive business was an incentive to continue adopting coconut ash organic fertilizer technology in his subsequent farming activities.DOI: https://doi.org/10.26905/abdimas.v6i1.4988